Rising Resistance: UTI Pathogens in Elderly Patients in a Rural Hospital of Maharashtra, India - Tamboli, Sabiha S (International Journal of Human and Health Sciences (IJHHS), 2025)
Background: Urinary tract infections (UTIs) are a significant health issue among elderly patients. Age-related changes, existing comorbidities, and frequent catheter use heighten the risk of UTIs in this cohort. Objective: This study aimed to identify the bacteriological profile and antibiotic resistance patterns of UTI pathogens in elderly patients from a rural tertiary care hospitals of Maharashtra, India. Methods: This cross-sectional study was conducted, among 300 elderly patients (aged 60 years and above) with clinically suspected UTIs. Midstream urine samples were aseptically collected and cultured using standard media. Bacterial identification was performed using the Kirby-Bauer disc diffusion method, adhering to CLSI guidelines. Results: Among the 300 samples, 250(83.3%) exhibited significant bacterial growth. Escherichia coli was the most prevalent isolate (45%), followed by Klebsiella pneumoniae (20%), Proteus mirabilis (12%), Pseudomonas aeruginosa (10%), Enterococcus faecalis (10%), and Staphylococcus aureus (3%). High antibiotic resistance rates were observed for beta-lactams such as amoxicillin (90% for E. coli), ciprofloxacin (70%), and ceftriaxone (60%). Carbapenems showed the lowest resistance across major isolates, with only 10% resistance reported for E. coli. Colistin and amikacin remained highly effective, with multidrug resistance rates below 10%. Conclusion: The study revealed that E. coli is the predominant pathogen in UTIs among elderly patients, exhibiting significant resistance to antibiotics like amoxicillin and ciprofloxacin. These findings highlight the necessity of routine urine culture and sensitivity testing to guide empirical treatment and emphasize the need for stringent antibiotic stewardship to combat rising resistance rates. International Journal of Human and Health Sciences Vol. 09 No. 03 Jul’25 Page: 185-190